Kepemimpinan Kepala Sekolah dalam Mewujudkan Merdeka Belajar di Sekolah Menengah Atas - Juita, Dince Putri; Ali, Hadhriyatul Amni; Asmendri, Asmendri; Sari, Milya (Indo-MathEdu Intellectuals Journal, 2024)
The leadership of the principal has a very important role in school management and has a decisive position in order to achieve the educational goals of the education unit. The purpose of this study is to find out how the role and position of the principal's leadership in realizing Merdeka Belajar. Merdeka Belajar is a program launched by the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia. Merdeka Belajar is a concept of educational development where all stakeholders are expected to become agents of educational changeThis research conducts literature studies by collecting materials from books, journals, articles and other sources related to the principal's leadership in realizing They Study in high school. The results of the analysis show that it shows that the principal as a leader becomes a policy director in achieving school goals. The principal as a leader has a very important role and position in decision making and is responsible for realizing school achievements in implementing Merdeka Belajar